Teachers’ Experiences in Using Digital Media for Learning to Support Quality Education in SDG 4 at SDN Pejaten Timur 05 - Sri Agustina (Indonesian Student Association Study Center in Türkiye, 2025)
This study explores teachers' experiences with using digital media for learning at SDN Pejaten Timur 05 and its contribution to supporting Sustainable Development Goal (SDG) 4: Quality Education. A qualitative approach with a case study design was used to gain in-depth insights into the subjective experiences of individuals regarding this phenomenon. The participants in this study were three teachers. Data were collected through in-depth interviews conducted online via Zoom Meeting. An interview guide was used as the data collection tool, and the interviews were recorded to ensure the accuracy of the information. Data were analyzed using an inductive approach, following the stages of transcription, pattern identification, and conclusion drawing. The results indicate that while the use of digital media enhances learning interactivity, teachers face challenges related to limited internet access, technology devices, and readiness to use technology. School support in providing facilities and infrastructure has been helpful, but there is a need to increase the availability of devices and ensure more stable internet access. This study offers recommendations to improve policies and digital infrastructure to better support inclusive and quality education in line with SDG 4.